British Thoracic Society Training Standards for Thoracic Ultrasound (TUS). Issue 1 (19th May 2020) - Stanton, Andrew E; Edey, Anthony; Evison, Matthew; Forrest, Ian; Hippolyte, Sabrine; Kastelik, Jack; Latham, Jennifer; Loewenthal, Lola; Nagarajan, Thapas; Roberts, Mark; Smallwood, Nicholas; Park, John E S
Abstract : Introduction: The British Thoracic Society (BTS) responded to a call from the pleural community to establish this new Training Standard to detail the capabilities in practice for thoracic ultrasound (TUS), which will build on the previous curricula and extend the remit to include training for the emergency provision of TUS. Methods: BTS convened a working group to produce a set of Training Standards. Results: This document provides a comprehensive Training Standard for TUS facilitating timely and improved management of patients with respiratory presentations, particularly (but not exclusively) pleural pathologies. Discussion: The Training Standards document will be widely disseminated.